EFEKTIVITAS PENGGUNAAN MEDIA VISUAL DALAM PEMBELAJARAN BAHASA INDONESIA DI SEKOLAH DASAR - Handayani, Reni (Universitas Sulawesi Tenggara, 2023)
The use of visual media in learning Indonesian in elementary schools has been proven to improve students' understanding of learning materials. This study aims to analyze the effectiveness of visual media, such as images, animated videos, and infographics, in supporting the process of learning Indonesian. The method used is a literature study by analyzing previous studies. The results of the study indicate that visual media can improve learning motivation, critical thinking skills, and students' understanding of the material. Therefore, the use of visual media is recommended as an innovative learning strategy in elementary schools.